Notary Roles and Liabilities Related to The Delivery of Information About the Beneficial Owners of Limited Liability Companies - Rama Prima Yoga; Rouli Anita Valentina (LEGAL BRIEF, 2022)
In the event of participating the Financial Action Task Force recommendation, Indonesian Government issued Peraturan Presiden Nomor 13 Tahun 2018 on the Penerapan Prinsip Mengenali Pemilik Manfaat atas Korporasi dalam Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang dan Tindak Pidana Pendanaan Terorisme which required limited company to deliver the information regarding beneficial owner. In relation of this issuance, there are 2 significant problems that we can study further. Firstly we can look at the regulation on delivering the information of beneficial owner of a limited company. Second, how is the role and obligation of Notary regarding the delivery of the information. This research is made by using a juridical normative method with secondary data consisted of primary law substance and secondary law substance as the base of the research. Based on this research, we can conclude that Limited Company must apply the principle of recognizing its beneficial owner. Notary has an important role in delivering the information on the beneficial owner of the company. But, Notary do not have the responsibility for the factual integrity of the beneficial owner that is provided by the company. With that in mind, it is better to apply a strict penalty or sanction for limited company that violates the regulation. Other than that, socialization on the practice of Peraturan Presiden Nomor 13 Tahun 2018 will be beneficial for the limited company.